SPIRITUAL ENTREPRENEURSHIP VALUES IN STUDENT LIFE SKILL LEARNING OF ISLAMIC BOARDING SCHOOL - Aida Nurcholida; Sugeng Hadi Utomo; Agus Hermawan (International Journal of Economy, Education and Entrepreneurship, 2022)
Islamic boarding schools have now become religious, educational institutions integrated with the local community. In line with the development in an ever-increasingly advanced era, it requires the santri students to have additional skills that can be useful when they graduate. Combining religious knowledge with entrepreneurship can complement each other and enrich the existing theory and practice of entrepreneurship because religion has now become an important element in social life. The research is conducted at the Fathul Ulum Islamic Boarding School in Jombang using qualitative research. The researcher's data collecting method is observation, interviews, and documentation. This research aims to learn how to learn life skills in growing Spiritual Entrepreneurship in students. The result of this research is that the Fathul Ulum Islamic Boarding School Jombang provides life skill learning through several business activities such as animal husbandry, fisheries, and agriculture, where in its application, the spiritual values ​​of entrepreneurship are contained in the nature that has been exemplified by the Prophet Muhammad SAW as a role model for Muslims with values Siddiq, Amanah, Tabligh and Fathonah